Acute morbidity profile and treatment seeking behaviour among people residing in an urban resettlement colony in Delhi, India (Nepal Journal of Epidemiology, 2018)
Background: Rapid urbanization has resulted in increased burden of communicable and non-communicable diseases, especially among urban poor population. In the absence of a well-functioning three tier health care system in urban India, health needs of urban poor are rarely fulfilled. The objective of this study was to assess primary health care services utilisation pattern and its associated selected socio-demographic determinants in an urban population of Dakshinpuri Extension, South-east district of Delhi.Materials and Methods: A community based cross-sectional study was done from November 2013 to November 2014 with a sample size of 440 households through simple random sampling. Information was obtained regarding the socio-demographic characteristics and morbidity pattern of all the members of household in the preceding one year of the conduct of the present study through a pretested semi structured interview schedule. Association of various socio-demographic characteristics with primary and secondary health care facilities utilisation was studied with bivariate and multivariate logistic regression.Result: In this study, 42% of the household members suffered from acute illnesses and symptoms in the preceding one year. Secondary/tertiary health care facilities were approached mostly for seeking treatment. Majority of the household members sought treatment from private health care facilities. Significantly higher utilisation of secondary/tertiary health care facilities was found by head of households and household members who are married.Conclusion: Primary health care system needs to be revamped to improve healthcare delivery among urban population. Strategies to decongest secondary/tertiary health care facilities in urban India needs focus.